Pentingnya Peranan CIA Triad Dalam Keamanan Informasi dan Data Untuk Pemangku Kepentingan atau Stakholder - Harahap, Abdul Halim Harahap; Andani, Claresta Difa; Christie, Angelia; Nurhaliza, Divtyajeng; Fauzi, Ahmad (Jurnal Manajemen dan Pemasaran Digital, 2023)
In the sustainability of an organization or company it is important to protect assets related to the organization or company being run. Important assets of companies and organizations include things that ensure the sustainability of an organization and the company itself. Information and data related to an organization or company is the most important thing to protect its security. In protecting information and data security, this paper discusses specific indicators of organizational or company security. This security indicator is known as the "CIA Triad" of Confidentiality, Integrity, Availability. In this study discusses CIA TRIAD in protecting information and data security in an applied system. These three factors are interrelated and maintain bonds with each other, in other words if one of these factors is eliminated Information and data security will be very risky. Therefore, the CIA Triad linkage is very important and has influence.